Analisis Kestabilan Heap Leach Pad Berdasarkan Jumlah Material Yang Dapat Ditampung Pada Projek Tambang XX, Jawa Barat - Razak, Supardi; Kusumaningsih, Dewi Ayu (Mining Science And Technology Journal, 2023)
The XX mining project is one of the gold mining companies in Indonesia that uses the heap leaching method to separate gold from other rocks. But it turns out that this heap leaching pile has a maximum capacity with a total volume of 14000 m3. In order to obtain an optimal slope design from a current slope condition on the planned location of the Heap Leach Pad in the XX mining project so that the cause of the heap failure can be determined with certainty, a geotechnical analysis was carried out referring to the Decree of the Minister of Energy and Mineral Resources Number 1827 K/30/MEM/2018 . In this study, slope stability analysis was carried out using the boundary equilibrium method. The data used is secondary data obtained directly from the XX mining project and laboratory test data. Tests carried out in the laboratory are to determine the value of rock density and shear strength test to determine the value of the inner shear angle and rock cohesion. In the slope modeling, the condition of water pressure is assumed to be maximum and the slope of the heap leaching pile is composed of soil and propylene. From the results of the analysis it was found that the slope was in an unstable condition when the heap leaching capacity was 11000 m3. So it needs to be handled, namely providing recommendations by reducing the height of the slope which was originally 1 meter to 0.5 meters. Keywords: Heap Leaching, Slope Stability, Boundary Equilibrium Method